Effect of vertical vibration stimulation at different frequencies on delayed muscle soreness in athletes: A randomized trial - Cheng, Liang; Wang, Kun; He, Benxiang; Yan, Yang (Frontiers in Public Health, 2022)
Background The effect of stimulation with different vibration frequencies on delayed muscle soreness (DOMS) has not yet been determined. This study was conducted to investigate the effect of medium- and high-frequency vertical vibration stimulation on DOMS in track and field athletes. Methods A total of 38 elite men's track and field athletes were recruited during the off-season. Through the digital randomization method, the participants were divided into three groups. Two-knee DOMS modeling was performed on the medium-frequency group (MFG, 25 Hz, n = 13), high-frequency group (HFG, 50 Hz, n = 12) and control group (CG, 0 Hz, n = 13). The three groups were matched in age, height and body mass. Vertical vibration stimulation was performed for 10 min on the MFG and HFG. Visual analog score (VAS); interleukin-6 (IL-6), lactic dehydrogenase (LDH) and creatine kinase (CK) levels and knee extension peak torque (PT) were determined immediately and at 24, 48, and 72 h after vibration. Results The 48 and 72 h VASs of the HFG were lower than those of the MFG and CG. The immediate and 24 and 48 h IL-6 concentrations in the HFG were lower than those in the CG. The 24 h IL-6 concentration in the HFG was lower than that in the MFG and that in the MFG was lower than that in the CG. LDH concentrations at different time points did not differ amongst groups. Immediate and 24 h CK concentrations were lower in the HFG than in the CG. The immediate and 24, 48, and 72 h knee extensions at 60°/s PT were lower in the HFG than in the CG. The immediate and 24 and 48 h knee extension at 60 °/s PT in the MFG were lower than those in the CG. The 24 h knee extension (240°/s peak torque) value in the HFG was lower than that in the CG. Conclusion Stimulation with 50 Hz (amplitude of 3 mm) vibration can reduce the muscle pain, IL-6 and CK concentrations and knee extension loss caused by DOMS. However, stimulation with 25 Hz (amplitude of 3 mm) vibration had poor effects. Results suggested that high-frequency vibration training is an effective strategy for relieving DOMS after intensive training.